HOW TO IMPROVE SPEAKING SKILL WITH THE HELP OF INNOVATIVE TECHNOLOGY - Rustamova, Adash Eshankulovna; Rakhmatullaeva, Sevinch Navruzjonovna (INTERNATIONAL CONFERENCES, 2023)
This article is devoted to the planning teaching language, especially, improving speaking skill to students who have it as a non-native language with the help of modern innovative and professional, pedagogical technologies (for instance interactive robot) and it can be assistant to teachers and offers some chances, such as it can make strong communication with students and improve students’ speaking skill, not only students, but also teachers’ qualifications. Because it can make healthy completion with teachers. Teachers cannot speak like native speakers, while by robot, students have this chance. Therefore, since the 21st century is age of information technology, robots are entering almost every field and it should also apply this to speaking classes.